2013
DOI: 10.4103/0019-509x.123601
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracorporeal irradiation in malignant bone tumors

Abstract: Results of our study suggest that ECI is technically feasible in the management of MBT and provides decent local control and short-term survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Another previous study by Kamal et al [1,7] reported a five-year survival rate of 54.97 ± 9.8% for LSS using ECI, while Sharma et al [31] affirmatively reported a survival rate as high as 64% for the same surgical technique. Patients with tumor size < 8 cm in diameter with a good type of Huvos always had a better survival rate than those with tumor size > 8 cm in diameter with a poor type of Huvos [1,37].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another previous study by Kamal et al [1,7] reported a five-year survival rate of 54.97 ± 9.8% for LSS using ECI, while Sharma et al [31] affirmatively reported a survival rate as high as 64% for the same surgical technique. Patients with tumor size < 8 cm in diameter with a good type of Huvos always had a better survival rate than those with tumor size > 8 cm in diameter with a poor type of Huvos [1,37].…”
Section: Discussionmentioning
confidence: 92%
“…Local recurrence also reported as high as 20% [7]. Sharma et al [31] reported an infection rate of 14%. Infection can result into delayed/non‐union of the bone graft, failure of the graft, and delay in the subsequent course of chemotherapy and therefore every effort should be done to minimize the infection [30].…”
Section: Discussionmentioning
confidence: 99%
“…[33] Limb preservation surgery requires special attention to evade future limb length discrepancy in pediatric patients. ECI can effectively prevent the growth of discrepancy frequently observed in prosthetic replacement by evading resection of the normal growth plate and interstitial bone growth from surrounding healthy bones.…”
Section: Managementmentioning
confidence: 99%
“…[34] The main benefit of ECI is the specific structural fit of reimplanted bone part and conservation of joint flexibility. [3334] The reimplantation of the irradiated bone averts some difficulties associated with allograft such as the accessibility of right graft from a bone bank, particularly for pediatric patients, graft rejection, and hazard of viral infection. [34] An autograft is defined as tissue grafted into a new position in the body of the same individual.…”
Section: Managementmentioning
confidence: 99%
“…We also reviewed some recent reports using different techniques to treat primary malignant musculoskeletal tumor, and the MWA therapeutic alternative has more advantages such as ablation in situ, reliable devitalization, less implants requirement, and less osteotomy requirement. The postoperative functional evaluation of MWA showed more superior outcomes than other therapeutic strategies, such as devitalizing autologous tumor-bearing bone in 99% alcohol for 30 min in vitro [10], in 20% sterile saline at 65 °C for 30 min [11], extracorporeal irradiation with X-rays [12], alcohol devitalization combined with prosthesis [13], prosthesis replacements [14], or other biological reconstruction after wide surgical resection [15].…”
Section: Functional Resultsmentioning
confidence: 99%